Modern restful api dls and frameworks for restful web services api schema modeling, documenting, visualizing - Malakhov, K.; Kurgaev, A.; Velychko, V. (Проблеми програмування, 2018)
The given paper presents an overview of modern RESTful API description languages (belongs to interface description languages set) – OpenAPI, RAML, WADL, Slate – designed to provide a structured description of a RESTful web APIs (that is useful both to a human and for automated machine processing), with related RESTful web API modelling frameworks. We propose an example of the schema model of web API of the service for pre-trained distributional semantic models (word embeddings) processing. This service is a part of the “Personal Research Information System” services ecosystem – the “Research and Development Workstation Environment” class system for supporting research in the field of ontology engineering: the automated building of applied ontology in an arbitrary domain area as a main feature; scientific and technical creativity: the automated preparation of application documents for patenting inventions in Ukraine. It also presents a quick look at the relationship of Service-Oriented Architecture and Web services as well as REST fundamentals and RESTful web services; RESTful API creation process. В статті наведено огляд сучасних мов опису веб-сервісів – OpenAPI, RAML, WADL, Slate – які призначені для подання структурованого опису сучасних веб-сервісів (веб-API), як для їх автоматизованої обробки програмними застосунками, так і для сприйняття розробником програмного забезпечення. Розроблено модель (схему) веб-API сервісу процесінгу дистрибутивно-семантичних моделей, який є частиною екосистеми сервісів "Персональної науково-дослідницької інформаційної системи" – системи класу Автоматизоване робоче місце наукових досліджень АРМ-НД підтримки науково-технічної творчості та досліджень в області онтологічного інжинірингу. Представлено короткий погляд на сучасне становище веб-сервісів в складі Сервіс-орієнтованої архітектури та на їх взаємодію. Також представлена методика опису веб-сервісів за допомогою сучасної мови структурного опису взаємодії інтерфейсів сервісів. В статье представлен обзор и сравнительный анализ современных языков описания веб-сервисов – OpenAPI, RAML, WADL, Slate – которые предназначены для представления структурированного описания современных веб-сервисов (веб-API) и разработаны с учетом применения как для их автоматизированной обработки описаний программными приложениями, так и для восприятия разработчиками программного обеспечения. Разработана модель (схема) веб-API сервиса процессинга предобученных дистрибутивно-семантических моделей, который является частью экосистемы сервисов "Персональной научно-исследовательской информационной системы" – системы класса Автоматизированное рабочее место научных исследований АРМ-НИ поддержки научно-технического творчества и исследований в области онтологического инжиниринга. Приведен короткий обзор современного положения веб-сервисов в составе Сервис-ориентированной архитектуры и на их взаимодействия. Также представлена методика описания веб сервисов при помощи современного языка структурного описания взаимодействия интерфейсов сервисов.